ANALISIS PRODUKTIVITAS PEKERJA PADA PROYEK PEMBANGUNAN WORKSHOP OPERATOR CRANE DI BALAI LATIHAN KERJA (BLK) KOTA SAMARINDA - RACHMAWARTI, NOVITA (KURVA S JURNAL MAHASISWA, 2019)
Knowing Novita Rachmawarti, 2019, Worker Productivity Analysis on Construction Projects of Crane Operators at Samarinda City Training Center (BLK), Thesis, Civil Engineering Department, Faculty of Engineering, University of August 17, 1945. Productivity is a fundamental factor that influences the performance of competitiveness in the construction industry. Labor productivity will also greatly affect the magnitude of the profits or losses of a project. In the implementation of the field this can sometimes occur because the workforce is less effective in its work. In measuring the level of productivity of labor there are various ways, one of which is by examine the magnitude of the level of LUR (Labor Utilization Rate) of each worker, which is to examine the extent of the effectiveness of the worker at work. The level of worker productivity is influenced by many factors. These factors include field conditions and supporting facilities, skills of workers, age or age factors of workers, suitability of wages, experience in work, health of workers, coordination and planning, types of work contracts, managerial or field management. This study was intended to analyze data by conducting a survey in the field, the existing data was collected and processed and then analyzed using the SPSS program (Statistical Package for Social Science) version 17. To obtain conclusions that were in accordance with the actual conditions in the survey location. In this study observations were carried out using the productivity rating method, where worker activity was classified into 3 things: Essential Contributory Work, Effective Work, and Not Useful. This research was conducted on Crane Operator Development Project at Samarinda City Training Center (BLK). The study was conducted by observing the level of productivity of 30 workers and accompanied by filling in questionnaires. Productivity level observation (LUR) is carried out for 12 days for each worker. Based on the results of the analysis, it can be concluded that the level of worker productivity in the Crane Operator Construction Workshop project at the Samarinda City Training Center (BLK) is quite satisfactory because of the average. Its productivity is 84.72%> 50%. This is in accordance with the book (Oglesby, 1989: 180-181) which contains "for a work team it is said to reach effective or satisfying time if the worker utility factor is more than 50%". Partially the variable that has a significant effect is the level of education with sig = 0.226> 0.05, the education level variable partially does not have a significant effect on the dependent variable of worker productivity. The level of education has a dominant influence with a beta value of 0.430 with a T value of 1,248.